Implementation as theory, hierarchy as transformation, homology as synapomorphy - Ebach, Malte C.; Williams, David M.; Vanderlaan, Tegan A. (Zootaxa, 2013)
Presently cladistics is based on, and justified by, a computer implementation (Wagner Parsimony) rather than sound methodological or theoretical foundations. In this paper, the recent goals of cladistics that are derived from computer implementations and ‘tree-thinking’ are discussed. The discussion raises a critical point, namely whether one can dispense with these recent goals and adopt a wholly systematic approach, one herein termed systematic thinking.